Blooming Stimulation of Microcystis in Sutami Reservoir Using Nutrients Nitrate and Phosphate in Different ratio - Catur Retnaningdyah; Suharjono Suharjono; Agoes Soegianto; Bambang Irawan (Journal of Tropical Life Science, 2010)
Microalgae Cyanobacteria from the genus Microcystis has the potential to bloom in Sutami reservoirs that located in Malang, Indonesia at a particular time. Microcystis is a notorious species because it can produce toxins that are dangerous to other organisms. The objective of this research is to determine the influence of different ratios of Nitrate and Phosphate on the growth of Microcystis in Sutami reservoir. The study was conducted from April to November 2009 and was carried out in situ in the reservoir Sutami with quasi experiment using a completely randomized design. Sutami reservoir water which already contained plankton community therein, including Microcystis were treated with five variations ratio of Nitrate and Phosphate (10, 20, 40, 80, and 160) and untreated water as control. Experiments carried out by using a transparent plastic bag diameter 1 m and 1.5 m long, inserted into the water and be immersed in the water by using bamboo. Calculation of Microcystis abundance and physic-chemical quality of water is done every three days for a month. The results showed that the higher concentration of orthophosphate in the media water of Sutami reservoir have the maximum abundance of Microcystis. Abundance of Microcystis grown in Sutami reservoirs have positively correlated with actual levels of nitrate, nitrite, total phosphate, conductivity, pH, temperature, ratio of Nitrate to Phosphate treatment and water KMnO4 value.Keywords: Blooming Microcystis, the ratio of nutrients Nitrate to Phosphate, Sutami reservoir